Investment in digital infrastructure: Why and for whom? - Don J. Webber; Ellen Hughes; Gail Pacheco; Glenn Parry (REGION, 2022)
This study investigates the variation in attitudes across stakeholders towards investments in the digital economy. Using semi-structured interviews to identify attitudes about the spatially evolving socioeconomic importance of the digital economy in New Zealand, we identified seven distinct yet partially overlapping concerns that prioritise preferences for digital investment. A key finding is that there are important asymmetries in stakeholders' narratives and epistemological foundations that currently align to collectively strengthen resolve to invest in digital infrastructure and training, but this alignment may splinter in future. Some stakeholders saw internet access as coalescing social economy, and there were concerns that some people and some places would get left behind if access is not rolled out uniformly and as a priority. There were disagreements about who will prosper, who will get left behind, who should pay for upgrading digital skills, the extent that investments were connected with wellbeing and identity, whether fake news was significant, and the longevity of the impact of digital economy investments. This study contributes to theory by demonstrating that practically-relevant, socially-informed policy decisions can be underpinned by collective efforts that draw on heterogeneous narratives and multidimensional understandings.
Keywords: D83; L86; L96; O18; R58; 330; nternet; Infrastructure; Wellbeing; Left behind; Places; People; Epistemology